PENGEMBANGAN MEDIA BERBASIS ANDROID UNTUK MENUNJANG PELAKSANAAN PEMBELAJARAN PADA MASA PANDEMI DI KELAS V SEKOLAH DASAR - Hayati, Syahida; Fachruddin, Farida; Desyandri, Desyandri (Universitas Pakuan, 2021)
This research is motivated by the problems faced by elementary school students in learning, especially in the implementation of learning during the pandemic, the lack of understanding of students on the materials and media used has not been integrated with students' daily lives. The type of research is research and development. The development model used is the ADDIE model. The results of the research using the developed android have valid, practical and effective categories. The results of the validity test showed that the average growth development was 87.97 in the very feasible category. The results of the observation of the implementation of the RPP obtained a percentage of 93% in the very practical category. The teacher's response questionnaire obtained a percentage of 90.63% which was very practical. The student response questionnaire obtained an average score of 93.2% in the very practical category. Thus, it can be said that the media using android to support learning during the pandemic for grade V elementary school students can be declared valid, practical, and effective.